Teatralidades de la Memoria a 50 Años del Golpe - Del Campo, Alicia (Teatro, 2024)
This essay reaffirms the notion of theatricalities of memory as a specific area of study within social theatricalities. It has evolved inrecent years as various forms of artistic and political intervention aimed to preserve social memory. Within this framework, the essay explores different commemoration strategies and interventions in public spaces developed during the 50th commemoration of the coup d'état in Chile.